Interpretasi Electrical Resistivity Tomography (ERT) untuk Pendugaan Air Tanah Dangkal pada Formasi Gunungapi Muda - Erik Febriarta; Suswanti Suswanti; Sembodo Noviandaru (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2019)
Aquifers or groundwater saturated areas in the slope morphology of Merapi volcano are relatively thin due to massive rock outcrops above the surface. Because these massive igneous rocks dominate the local geological appearance, the groundwater potential on the upper foot slope is relatively lower than the lower one that has thicker aquifer materials (sand). This study was designed to investigate the thickness of potential groundwater and identify the aquifer materials by geoelectrical methods using the Electrical Resistivity Tomography (ERT) configuration. ERT has several advantages, including its ability to present multi-log lithology vertically and produce a more detailed surface appearance. In this study, rock resistivity values were measured with a survey line stretching across 250 m. The geoelectrical imaging produced actual values (potential values) of the rock resistivities through the matching curve and inversion techniques. Afterward, the actual resistivities were matched with the standard electrical resistivity of rocks and their respective hydrogeological characteristics, i.e., the capacity to store and transmit water. Interpretation on rock resistivities detected groundwater at a depth of 0.5-12 m in Manisrenggo. This shallow aquifer has an impermeable layer composed of igneous rocks, which are massive breccia, that lie in one layer of sand. According to the Groundwater Basin Map, these rock formations are part of the Karanganyar-Boyolali Groundwater Basin. The shallow aquifers and hydraulic gradient lead to the emergence of seeps or flushes on the soil surface.